2019
DOI: 10.1080/10967494.2019.1622613
|View full text |Cite
|
Sign up to set email alerts
|

Is Private Production of Hospital Services Cheaper than Public Production? A Meta-Regression of Public Versus Private Costs and Efficiency for Hospitals

Abstract: The question of whether private organizations can outperform public ones in public service delivery has been a major topic of interest over the last few decades. However, the empirical evidence does not systematically support the hypothesis of lower costs and higher efficiency when private organizations deliver public services. To better understand the cost and efficiency differences between public and private organizations, we have conducted a metaregression analysis of econometric studies relating to hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…The adoption of a differentiation or a cost leadership business strategy depending on the lack or existence of a universal healthcare system is congruent with the findings of Lin et al [23], that Taiwanese privately owned hospitals bear lower operational costs than those owned publicly, and those of Woolhandler et al [24] showing that the costs of delivering health services are higher for US private hospitals than for Canadian private hospitals [25]. These operational costs could increase due to the implementation of high-tech medical technologies as a differentiation business strategy [26], allowing them to grow their revenues proportionately, justified by a higher value added of rare and imperfectly imitable medical technology resources that provide them with a competitive advantage, enhancing long-term corporate financial performance according to the firm resource-based theory [27].…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 73%
“…The adoption of a differentiation or a cost leadership business strategy depending on the lack or existence of a universal healthcare system is congruent with the findings of Lin et al [23], that Taiwanese privately owned hospitals bear lower operational costs than those owned publicly, and those of Woolhandler et al [24] showing that the costs of delivering health services are higher for US private hospitals than for Canadian private hospitals [25]. These operational costs could increase due to the implementation of high-tech medical technologies as a differentiation business strategy [26], allowing them to grow their revenues proportionately, justified by a higher value added of rare and imperfectly imitable medical technology resources that provide them with a competitive advantage, enhancing long-term corporate financial performance according to the firm resource-based theory [27].…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 73%
“…The practice of overcharging or price gouging has been reported from some High Income Countries (HICs) too [ 62 ]. Some reviews from HICs have concluded that the charges taken by for-profit providers tend to be much higher than their cost of production [ 63 ]. Such findings can have implications for the allocative efficiency in health systems [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews from HICs have concluded that the charges taken by for-profit providers tend to be much higher than their cost of production [ 63 ]. Such findings can have implications for the allocative efficiency in health systems [ 63 ]. The current study suggests that this might be the case in India too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International reviews of literature on privatization of government services show that results in terms of cost-saving are mixed (Bel and Warner 2008;Boyne 1998) and consequences for consumers in terms of prices and efficiency and quality of service delivery are inconclusive and most often not included in assessments at all (Petersen, Helby, and Vrangbaek 2018). For instance, in the United States and Europe, partial contracting out to private-health-service delivery firms did not increase cost-effectiveness and efficiency of the health services delivered (Bel and Esteve 2019).…”
Section: Introductionmentioning
confidence: 99%